BETTER TEACHING AND LEARNING IPA UNTUK MENGEMBANGKAN KARAKTER DAN KEMAMPUAN BERPIKIR SISWA SMP - Dwi Yulianti; Siti Harnina Bintari (Universitas Negeri Semarang, 2013)
This Classroom Action Research aims to developed the character and critical thinking ability of junior high school student through learning model better teaching and learning (BTL). The research included three cycles, planning, action and observation and reflection. The research subject is VII B class and XI A SMP Negeri 13 Semarang. The data obtain from observation sheet, test, and questionaire. The research result that obtained application BTL can be developed character and critical thinking ability although the criteria is medium range. This is possibly happened because the character and critical ability are the habit that should be trained repeatly and continously. Consequently, it is need more research to increase chracater and critical ability that more significant.